Lifelong learning : issues of effective implementation - Lee, S.T.; Chia , B.C.; Nik Hasnaa , Nik Mahmood (2011)
Lifelong Learning is becoming more important as the median age of the world and the pace of change continues to increase. It has become part of key national development strategy to update and upgrade the knowledge of its citizen to meet the challenges of globalization. This paper reviews the goals and process of lifelong learning, which may be academic or nonacademic, pre-employment or post-employment, formal, semi-formal or informal. It then examines the deployment of modern information communication technology (ICT), and its effects of accelerating the life-long learning process. Among the modes of delivery, the authors contended that Open and Distance Learning (ODL) with blended mode of delivery is perhaps the most effective means of implementing lifelong learning. The issues of assessment and accreditation, especially the validation and recognition of informal learning remain one of the main obstacles to the implementation of lifelong learning. (Authors' abstract)